Parent‐implemented multiple schedules. (27th August 2020) - Campos, Claudia; Bloom, Sarah E.; Weyman, Jennifer R.; Garcia, Anna R.
Abstract: Multiple schedules are compound schedules that alternate, and each schedule corresponds with a stimulus. They are effective at establishing stimulus control over behavior. Thus, they are sometimes implemented as schedule thinning procedures within the context of functional communication training (FCT) to reduce high rates of appropriate responses while maintaining problem behavior at low rates. To date, researchers have continued to evaluate the practicality of multiple schedules in clinical cases. However, there is a paucity of research on the generalization of treatment effects across settings and implementers. Thus, the purpose of this study was to (1) extend previous research by experimentally evaluating caregiver training on the implementation of multiple schedules within the context of FCT as a treatment for their children's problem behavior in their homes, and (2) assess the social validity of the multiple schedule with the parents. Three parent–child dyads participated in the study. All parents successfully learned to implement the multiple schedules in their home with their children. In addition, all parents reported that the treatment was highly acceptable.